Iceland, scale 1:425,000 : indexed : waterproof = Ísland, mælikvardi 1:450,000 : waterproof / cartography by Le Nhat Nam - Weit, Wencke ;International Travel Maps (Firm); ITMB Publishing Ltd. (Vancouver, B.C. : ITMB Publishing Ltd., 2006)
First edition. Relief shown by contours, gradient tints, and spot heights. Depths shown by gradient tints.; Panel title.; "[copyright] ITMB Publishing Ltd. 2006."; Includes inset of Reykjavík, index to places, publisher's list of maps, coverage diagram, notes, and col. ill. Color; 1:450,000